Resectable locally advanced gastric adenocarcinoma: interim analysis - Shanmugam, Subbiah; Kishore, Prem (International Surgery Journal, 2020)
Background: The MAGIC and ACCORD 07 trials have established the role of perioperative chemotherapy in locally advanced gastric adenocarcinoma. A more recent study has demonstrated the superiority of the FLOT perioperative regimen. The best strategy to improve outcomes has yet to be determined. Aims of the study were to evaluate perioperative chemotherapy in terms of morbidity and tolerance of FLOT regimen with modification and histopathological response Methods: This prospective study was started after ethical committee approval in February 2019 at a tertiary cancer center in South India for a period of 1 year up till February 2020. Patients fulfilling inclusion criteria were enrolled. Perioperative chemotherapy was given as scheduled regimen and adverse effects and response to preoperative chemotherapy were recorded. Radical D2 gastrectomy and histopathology assessed analysed by using IBM SPSS statistics ver. 21 and descriptive statistics used. Results: From February 2019 till February 2020, a total of 24 patients of newly diagnosed adenocarcinoma of the stomach of which 18 patients were nonmetastatic on workup. Moderately different (38.8%), well-differentiated in 11.2%, poorly differentiated in 50%. Total 66.7% were diagnosed as metastatic on staging laparoscopy, peritoneal wash cytology in 50% was negative. The cardiopulmonary resuscitation was seen in two patients. Conclusions: Even though it is an interim analysis with less number of patients enrolled, so far it can be concluded that all patients where surgery is planned should undergo peritoneal lavage cytology and FLOT regimen can be practised with acceptable morbidity. Long term results after completion of study will definitely throw more light.